Lysophosphatidic Acid (LPA) Signaling in Human and Ruminant Reproductive Tract - Izabela Wocławek-Potocka; Paulina Rawińska; Ilona Kowalczyk-Zieba; Dorota Boruszewska; Emilia Sinderewicz; Tomasz Waśniewski; Dariusz Jan Skarzynski (Hindawi Limited, 2014)
Lysophosphatidic acid (LPA) through activating its G protein-coupled receptors (LPAR 1-6) exerts diverse cellular effects that in turn influence several physiological processes including reproductive function of the female. Studies in various species of animals and also in humans have identified important roles for the receptor-mediated LPA signaling in multiple aspects of human and animal reproductive tract function. These aspects range from ovarian and uterine function, estrous cycle regulation, early embryo development, embryo implantation, decidualization to pregnancy maintenance and parturition. LPA signaling can also have pathological consequences, influencing aspects of endometriosis and reproductive tissue associated tumors. The review describes recent progress in LPA signaling research relevant to human and ruminant reproduction, pointing at the cow as a relevant model to study LPA influence on the human reproductive performance.